PENGEMBANGAN MEDIA PEMBELAJARAN ULAR TANGGA UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS VIII MATA PELAJARAN IPS DI SMP MUHAMMADIYAH 15 LAMONGAN - Amaliyah, Dewi Ayu (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
The problems that occurred in Junior High School Muhammadiyah 15 Lamongan is learners feel saturated with teaching methods of lectures from teachers without involving students to take an active role in learning. The students still lack creativity in learning IPS materials. This is because teachers are more active in the classroom by using lecture learning methods and learning media LKS. The purpose of this research is to: (1) to develop learning media of Snake Ladder social education subjects VIII grade Junior High School Muhammadiyah 15 Lamongan, (2) to know the feasibility of learning media Snake Ladder IPS subjects for grade VIII Junior High School Muhammadiyah 15 Lamongan students assessment of material experts and media experts. This thesis uses a research and development approach or Research and Development (RD) with the development model of ADDIE (Analysis, Design, Development, Implementation Evaluation. The result of the research is (1) The researcher conducting field trials conducted to 15 students in the experimental group class VIII Junior High School Muhammadiyah 15 Lamongan. The field trial prototype gets an 87% percentage so that it is converted to a valid qualification level. (2) The feasibility of the media engineering aspects of the 21 statements is categorized as feasible. Assessment of the lecturer is 75% interesting enough the level of validity can be used with small revisions. Thus media ladder snakes in the assessment of media experts worthy of use as a medium of learning junior high school students. (3) Media learning snake ladder on the material changes in Indonesian society during the colonial period and the growth of nationalism spirit can effectively improve the learning outcomes of students of class VIII SMP Muhammadiyah 15 Lamongan. By looking at the average control class is smaller than the experimental class on the post-test that is 1262 1355.Keywords:Â development learning; snake ladder; learning media